KEEFEKTIFAN PENGGUNAAN MEDIA GAME EDUKATIF ROGAPLAY TERHADAP MINAT DAN HASIL BELAJAR IPAS PESERTA DIDIK SEKOLAH DASAR - Rahmawati, Dewi; Muslimin Ibrahim; Asmaul Lutfauziah; Agus Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low interest and learning outcomes of students in science learning in elementary schools are often caused by the use of less varied learning media so that the learning process tends to be monotonous and less actively involving students. This study aims to determine the effectiveness of the use of Rogaplay educational game media on the interest and learning outcomes of elementary school students in science. This study uses a quantitative approach with a pre- experimental design of one group pretest–posttest. The study was conducted at Kyai Hasyim Elementary School, Surabaya, with 31 fourth-grade students as research subjects. Data collection techniques used tests, questionnaires, and observations. Analysis of learning outcomes was carried out using the N-Gain formula, while data on students' learning interests were analyzed using percentages. The results showed that the use of Rogaplay educational game media was effective in increasing students' interest and learning outcomes. The average N-Gain value of learning interest was 0.70, which is included in the high increase category. Meanwhile, the average N-Gain value of cognitive learning outcomes was 0.88, which is also included in the high increase category. Furthermore, the average psychomotor learning outcome was 93.06, indicating that students were able to effectively use Rogaplay media during the learning process. Therefore, Rogaplay educational game media can be used as an alternative, innovative learning medium to improve interest and learning outcomes in science in elementary schools.